Internet as an educational resource - Aleksandrova, K. V.; Vasylyev, D. A.; Shkoda, A. S.; Priimenko, B. A.; Александрова, Катерина Вячеславівна; Васильєв, Денис Андрійович; Шкода, Олександр Станіславович; Прийменко, Борис Олександрович (Х. : НФаУ, 2017)
Intro. Throughout history, educational environments have been the object of diverse transformations as strategies and media have changed. This fact reveals, undoubtedly, the communicative processes as fundamentals of education. The "information society" in general and the new technologies in particular have a significant impact on all levels of the world educational.
Keywords: тези